Saving Nelson Mandela the Rivonia trial and the fate of South Africa - Broun, Kenneth S. (Pivotal moments in world history., 2012)
When South Africa's apartheid government charged Nelson Mandela with planning its overthrow in 1963, most observers feared that he would be sentenced to death. But the support he and his fellow activists in the African National Congress received during his trial not only saved his life, but also enabled him to save his country. This book recreates the trial. It shows how outstanding advocacy and widespread public support backfired on apartheid leaders. Despite his 27 year incarceration, Mandela's ultimate release helped move his country from the racial tyranny of apartheid toward democracy.